THE NATURE AND CHARACTERISTICS OF BLOG FIELD AND JOURNALISM - Tursunova Khonzodabegim Khudoberdi kizi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article provides a systematic analysis of the content and current state of the blog industry. At the same time, the difference between the blog industry and today's traditional journalism is also calculated on a scientific basis, and to get feedback on the advantages and disadvantages of the blog industry.